2023
DOI: 10.1021/acs.est.3c01273
|View full text |Cite
|
Sign up to set email alerts
|

Using Mercury Stable Isotopes to Quantify Bidirectional Water–Atmosphere Hg(0) Exchange Fluxes and Explore Controlling Factors

Abstract: In this study, exchange fluxes and Hg isotope fractionation during water−atmosphere Hg(0) exchange were investigated at three lakes in China. Water−atmosphere exchange was overall characterized by net Hg(0) emissions, with lake-specific mean exchange fluxes ranging from 0.9 to 1.8 ng m −2 h −1 , which produced negative δ 202 Hg (mean: −1.61 to −0.03‰) and Δ 199 Hg (−0.34 to −0.16‰) values. Emission-controlled experiments conducted using Hg−free air over the water surface at Hongfeng lake (HFL) showed negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…However, the average isotopic compositions of the Hg(0) collected from the DFC outlet at night were similar to those collected during the day, as seen from the signature values presented above. This phenomenon may be because very little abiotic dark reduction occurs at night, and a delayed release of Hg(0) was previously produced during the day . Therefore, Hg(0) collected at night cannot be used as an endmember for abiotic dark reduction in the mixing model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the average isotopic compositions of the Hg(0) collected from the DFC outlet at night were similar to those collected during the day, as seen from the signature values presented above. This phenomenon may be because very little abiotic dark reduction occurs at night, and a delayed release of Hg(0) was previously produced during the day . Therefore, Hg(0) collected at night cannot be used as an endmember for abiotic dark reduction in the mixing model.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Hg(0) exchange flux between the paddy soil and the atmosphere was measured at Gouxi using the DFC method (Figure S4). , Sampling was performed on the 50, 90, and 110th day after transplanting and first flooding, with each sampling period lasting 24 h. Given the significant impacts of flooding and solar radiation on Hg(0) emissions from paddy soils, , day 50 and 90th were selected to assess the variations in Hg(0) emissions under different solar radiation intensities. Additionally, day 110th was chosen for sampling to examine the changes in soil Hg(0) emissions between flooded and dry conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that 60% of deposited snowfall-Hg can be re-emitted to the air and estimated that the ε 202 Hg of snow-released Hg of −0.53‰, and assumed the E 199 Hg and E 201 Hg of 1.40‰ representing the level of annual re-emission. g Mercury isotope fractionation in the oceanic environment remains unexplored. Model studies have indicated that Hg 0 released into the ocean is subject to isotopic alteration due to reduction processes occurring within the ocean. , Drawing from investigations into Hg II reduction in NOM-rich waters and freshwater–air Hg 0 exchanges, we hypothesize that oceanic reduction follows a similar fractionation pattern and assume the enrichment factors of ε 202 Hg = −0.13‰, E 199 Hg = E 201 Hg = −0.15‰. …”
Section: Methodsmentioning
confidence: 92%